Association of MOV10L1 gene polymorphisms and male infertility in azoospermic men with complete maturation arrest - Sarkardeh, Homa (Springer US, 2014)
PURPOSE: The present research was undertaken to study probable genetic variations of MOV10L1 in 30 infertile men that had complete maturation arrest in their spermatocyte levels and 70 fertile men as the control group. METHODS: We performed polymerase chain reaction single strand conformation polymorphism (PCR-SSCP) on extracted DNAs and sequencing was used to confirm the results. Identified polymorphisms in the MOV10L1 were further subjected to a haplotype analysis. RESULTS: We identified eight single nucleotide polymorphisms (SNPs): one missense (rs2272837) and four nonsense polymorphisms (rs2272836, rs11704548, rs2272838, rs138271) in the exonic sequences and three polymorphisms (rs12170772, rs2272840, rs17248147) in the intronic regions. With the exception of rs2272838, there was a statistically significant association in all polymorphisms between study population (P < 0.05). The result of haplotyping analysis showed ten possible haplotypes, from which five were significantly increased in infertile patients compared with the control group. CONCLUSIONS: Our results suggest that MOV10L1 gene polymorphisms in the studied infertile males with complete maturation arrest are linked to infertility.